(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The increasing prevalence of diabetes mellitus in recent years to the focus of public health interests in Bangladesh. Herbal medicinal plant such as mahogany and bitter melon can be used as alternative of synthetic drugs to avoid side effects and high cost. So the present study was undertaken to investigate the antidiabetogenic effect of bitter melon and mahogany on diabetic rabbits. Four months old rabbits were randomly assigned into five groups (T1, T2, T3, T4 and T5) with 4 rabbits. Group T1 was kept for negative (no alloxan) control, the rest of the group (T2, T3, T4 and T5) were injected with alloxan intramuscularly at a dose rate of 75mg /kg body weight. T2 was positive control group. Group T3, T4 and T5 was considered for bitter melon (150mg/kg b.w.), mahogany (50mg/kg b.w) and combined with previous dose respectively. Suspension of both fruit was tested for its efficacy in alloxan induced diabetic rabbit. Over the course of the trial, observations were recorded for induction of diabetics, blood glucose level, and body weight after 72 hours. Blood glucose level were increased significantly (p<0.05) in all treated groups compared to the control group and the highest induction was recorded in T2 group treated with alloxan. Body weight was decreased significantly (p<0.05) in all alloxan treated groups and lowest was recorded in group T2. There was significant decreased in blood glucose level in all bitter melon and mahogany treated group (T3, T4, T5) compared to the T2 group and lowest glucose level was recorded in T5 group. The present study reveals that combined treatment with bitter melon and mahogany decreases blood glucose level without affecting health of rabbits. The results of this study show that chronic oral administration of a suspension of bitter melon fruits and mahogany seeds in appropriate dosage may be good alternative as anti-diabetic agent. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 136-142